Behavior of precast reinforced concrete columns subjected to monotonic short-term loading - S. S. R. Pereira; H. Carvalho; J. V. F. Dias; V. R. Verga M.; P. A. Montenegro (Fracture and Structural Integrity)
This paper presents a case study on the behaviour of precast reinforced columns with non-conventional cross-section. An experimental program was developed to verify the serviceability and ultimate limit states of these columns, loaded with eccentric compression forces. In addition, results obtained through a theoretical model based on the Brazilian standard ABNT NBR 6118:2014 and a Finite Element numerical model using ANSYS software were presented. Analysis of the results showed that the proposed models satisfactorily predicted column behaviour. However, the ultimate strength of the column could not be determined due to limitations in the formulation of the theoretical model. The numerical model presented good agreement with the experimental results, both in serviceability and in ultimate limit state